Cover Feature: Highly Efficient Photocatalytic Conversion of CO2 to CO Catalyzed by Surface‐Ligand‐Removed and Cd‐Rich CdSe Quantum Dots (ChemSusChem 20/2019). Issue 20 (15th October 2019) - Xia, Wu; Wu, Jin; Hu, Jun‐Chao; Sun, Shanshan; Li, Ming‐De; Liu, Hongfang; Lan, Minhuan; Wang, Feng
Abstract : The Cover Feature shows a type of surface‐ligand‐removed and Cd‐rich CdSe quantum dots (LRCR‐CdSe QDs), represented by a moon because the CdSe QDs function as an active catalyst by receiving irradiation, like the moon receives light from the sun. The whole image reflects a beautiful moon night, in which the tower is the landmark of Wuhan (China). The QDs exhibit exceptional activity and selectivity in the conversion of CO2 to CO, benefiting from surface manipulation by improving the Cd/Se stoichiometric ratio and stripping surface organic ligands to expose more active Cd atoms. More information can be found in the Communication by W. Xia et al. onpage 4617 in Issue 20, 2019 (DOI:10.1002/cssc.201901633 ).